2021
DOI: 10.21203/rs.3.rs-654081/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Arctic has warmed four times faster than the globe since 1980

Abstract: In recent decades, the warming in the Arctic has been much faster than in the rest of the world, a phenomenon known as Arctic amplification (AA). Numerous studies report that Arctic is warming either twice, more than twice, or even three times as fast as the globe on average. However, the lack of consensus of AA definition precludes its precise quantification. Here we show, by using several observational datasets which cover the Arctic region and adopting a simple definition of AA, that during the last 40 year… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 62 publications
0
19
0
1
Order By: Relevance
“…This robust phenomenon known as Arctic amplification, emerged relatively recently (England et al, 2021) and is one of the prominent indications of climate change (Koenigk et al, 2020;Previdi et al, 2021). However, recently Rantanen et al (2021) showed that during the last 40 years the pace of Arctic warming is almost four times that of the globe as a whole, which is higher than previously reported. Arctic amplification occurs in all seasons except boreal summer, with the strongest warming in fall and winter (Cohen et al, 2020;Previdi et al, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…This robust phenomenon known as Arctic amplification, emerged relatively recently (England et al, 2021) and is one of the prominent indications of climate change (Koenigk et al, 2020;Previdi et al, 2021). However, recently Rantanen et al (2021) showed that during the last 40 years the pace of Arctic warming is almost four times that of the globe as a whole, which is higher than previously reported. Arctic amplification occurs in all seasons except boreal summer, with the strongest warming in fall and winter (Cohen et al, 2020;Previdi et al, 2021).…”
Section: Introductionmentioning
confidence: 90%
“…Глобальное изменение климата затронуло Фенноскандию: повысилась годовая температура воздуха, минимальные температуры в безморозный период, а также увеличился вегетационный период [Karlsen et al, 2009;Blinova and Chmielewski, 2015;Marshall et al, 2016;Rantanen et al, 2022]. В отношении осадков тренды плохо выражены [Aalto et al, 2016;Kivinen et al, 2017], однако изменение гидрологического режима заболоченных территорий прогнозируемо [Kreplin et al, 2021], и именно спад грунтовых вод может модифицировать продуктивность и состав сообществ бореальных болот [Mäkiranta et al, 2018].…”
Section: Introductionunclassified
“…Microbes are the main players in soil organic matter (SOM) decomposition and greenhouse gas production and consumption (e.g., carbon dioxide [CO 2 ], methane [CH 4 ], and nitrous oxide [N 2 O]) in thawing permafrost (Box 1). Air temperatures in northern high latitudes are warming faster than the global average (estimates range from 2–4x; Huang et al, 2017; Overland, 2016; Rantanen, 2021), increasing permafrost temperatures at a global scale (Biskaborn et al, 2019). Terrestrial permafrost regions contain an estimated 1400 to 1600 Pg of soil organic carbon (C), twice the amount in the atmosphere (Hugelius et al, 2014; Schuur et al, 2015, 2018).…”
Section: Introductionmentioning
confidence: 99%